Shifts in bacterial biodiversity along an environmental gradient in high-Arctic tundra - Düring, Aslak von (UiT Norges arktiske universitet, 2019)
Arctic soil microbiomes may have to face drastic climate changes in the coming century. Currently, the arctic tundra act as a carbon sink due to slow decomposition rates of soil organic carbon, which partly owes to low temperatures and poor water drainage. However, with elevated temperatures, large, latent carbon pools stored in arctic permafrost are exposed to mineralization by the active layer microbiota. This could cause increased emissions of potent climate gases, such as CH4 and CO2 to the atmosphere. Potentially changing the status of the arctic tundra into a net carbon source and further result in a positive feedback-loop to the climate system. Along with the climatic changes, altered precipitation regimes are predicted to cause higher water contents in some areas, while others are predicted to become drier. In turn, these changes are likely to trigger a response in the diversity and functioning of the soil microbial communities, which again might have an impact on biogeochemical cycles. Methane oxidizing bacteria (MOB) are bacteria that works as a filter for CH4, mainly produced by anaerobic methanogenic archaea. Some MOB also possesses the ability to consume CH4 from the atmosphere (atmMOB). Studies have shown that high water saturation might impede O2 availability, which is demonstrated to lower CH4 oxidation rates. Here we investigate how the bacterial biodiversity, and, in more depth, the MOB community changes along a moisture gradient in high-Arctic tundra, Svalbard. We have used next generation sequencing of the 16S rRNA gene, and the MOB functional gene, pmoA, to infer differences in community composition along the gradient. Statistical analyses were used to deduce the effect of environmental variables on the bacterial- and MOB community structure. Both moisture and pH were shown to have significant effects on the bacterial community composition. Proteobacteria, Actinobacteria and Acidobacteria were overall the most abundant phyla. Cyanobacteria had a high abundance in the top layer of wet soil, ...